A Critical Study on Emerging Legal Challenges of Genetic Engineering: Global Innovations and India’s Response - Ms. Maitrayae Sadhu; Dr. Papiya Golder; Dr Pranshul Pathak; Dr. Atul Jain; Dr. Neha Mishra (The Bioscan, 2025)
In the era of rapid technological development, the field of biotech is not running late. The development in the molecular biology has called for upgradation in modern biotechnology. One of the important aspects of molecular biology is the study with gene, and the inter-related materials. With the passage of time, study of human gene urge for therapy to cure certain genetic diseases. By the process of genetic engineering, one can edit or alter the gene which is responsible for that particular disease. However, now the science has upgraded in this manner where the process of genetic engineering is able to edit the germ line gene not for therapy but also able to design one’s baby according to their choice. Hence, the human are able to interfere the most natural process of the earth, creating new life. The paper thus would be focused on analyzing the international instruments in terms of procreation of designer baby and would further analyze the position of Indian feasibility of the designer baby.